Preferensi konsumen dan respon pedagang ubi jalar varietas Cangkuang di Kota Kendari Provinsi Sulawesi Tenggara - Muh. Taqwa; R. Marsuki Iswandi; Idrus Salam (Jurnal Sosio Agribisnis, 2023)
The Cangkuang variety of sweet potato is very much liked by consumers, but there are still many sweet potato varieties offered by traders that do not match consumer preferences. This study aims to determine: consumer preferences and the attributes that are most considered by consumers in purchasing decisions of the Cangkuang Variety sweet potato, and the response of traders to the Cangkuang Variety sweet potato consumer preferences. The population in this study were all consumers and traders of the Cangkuang variety of sweet potatoes. Determination of consumer samples was carried out by accidental sampling technique with a total sample of 35 people. The population of traders is 30 people, so that the entire population is used as a sample (census). The data collected includes consumer preferences for price, taste, size, cleanliness and shape as well as trader response data on consumer preferences. Data analysis was carried out using conjoint and qualitative descriptive. The results of the study showed that consumers preferred sweet potato Cangkuang variety with standard price, sweet taste, medium size, clean skin from soil and irregular oval shape. Attributes that consumers consider the most are price, size, taste, cleanliness and shape. While the response of traders to consumer preferences is that traders are willing to sell according to the wishes of consumers but must consider the benefits so as not to harm the traders.Keywords: consumers; trader; preference; response; cangkuang sweet potato variety